Comparison of human and bovine enamel in a microbial caries model at different biofilm maturations. (May 2020) - Ayoub, Hadeel M.; Gregory, Richard L.; Tang, Qing; Lippert, Frank
Highlights: The use of human versus bovine enamel when used in microbial caries models was explored. The use of nylon mesh to support even biofilm growth over enamel was evaluated. pH cycling can be utilized in in-vitro microbial cariogenic models using growth media as the demin and remin solutions. Human or bovine enamel specimens can be used in microbial caries models to study biofilm maturation and anticaries agents. The use of utility protective mesh over enamel samples prevents accurate evaluation of the biofilm. Abstract: Objectives: To compare human versus bovine enamel when used in microbial caries models; and to evaluate the use of nylon mesh to support biofilm growth over enamel. Methods: Twenty-four sub-subgroups were included (time factor: 4, 8, and 12 days; substrate factor: human/bovine; mesh factor: yes/no; treatment factor: 18.4 mM NaF (350 ppm F), de-ionized water [DIW]; n = 9/sub-subgroup). Microcosm biofilm from human saliva (IRB approval #1, 406, 440, 799) was grown on enamel specimens for 24-h (Brain Heart Infusion media; 0.2 % sucrose), using active attachment model. Then, pH-cycling took place. At the end of each pH-cycling period, enamel specimens were analyzed: surface microhardness (VHNchange ); transverse microradiography (integrated mineral loss [ΔZ], lesion depth [L]). Biofilm was analyzed: lactic acid production (LDH activity); exopolysaccharide (EPS) amount; and viability (12-day sub-groups). Data were analyzed using ANOVA at a 5 % level of significance. Results: The three-way interaction between pH-cycling duration, substrate type, and treatment type was significant for (VHNchange [p < 0.0005], ΔZ [p = 0.0027], and L [p < 0.0001]). VHNchange exhibited increased lesion severity as pH-cycling time increases, in both treatments. VHNchange data indicated a treatment effect in all timepoints. ΔZ and L exhibited higher values with more mature biofilms. ANOVA analyses for LDH and EPS indicated a significance between variables (LDH p = 0.0100; EPS p < 0.0001). Mesh-covered specimens resulted in lower LDH and EPS values in all maturations. ANOVA analyses of viability (12 days) between variables was significant. Conclusion: within the study's limitations, human or bovine enamel can be used in microbial in vitro caries models to study biofilm's maturation and anticaries agents. Clinical Significance: This study demonstrated how a known cariostatic effect of a fluoride concentration in toothpastes can be modulated by the maturation stage of oral biofilm. This can represent hard to reach areas in the oral cavity (e.g. in orthodontic patients or patients with intermaxillary fixation following oral and maxillofacial surgeries).